Cities in Europe and Central Asia : A Shifting Story of Urban Growth and Decline - Zhukova, Sofia; Restrepo Cadavid, Paula; Cineas, Grace; Quintero, Luis E.; Zhukova, Sofia (World Bank, Washington, DC, 2017)
This report is organized in four sections. Section one provides an overview of the context in which many ECA cities consolidated. This section includes a review of the key factors that shaped the urban systems of ECA, including a discussion of the implication of urbanizing under planned economies and a discussion of recent demographic trends (migration and fertility). This section also includes an overview of the contribution of the urban sector to ECA’s economy and the linkages between urbanization and economic development. Section two zooms into ECA’s urban systems and describes emerging trends in population and economic density using the Cities in ECA database. Among the observed trends, is the emergence of two opposing patterns in ECA’s urban system: one of (population) growth and one of decline. Section three takes a closer look at cities, comparing winners to losers, and parses through underlying factors that could explain their relative position. Finally, section four touches on the policy implications of the report’s empirical findings, highlighting how other countries and cities have managed decline and identifies potential follow-up work. The report is based on a unique city-level database that covers more than 5,000 cities in the region. The report does not intend to provide country specific or in-depthassessment at the sub-regional level, does not cover other angles of interest (firm-level analysis, household-level analysis) or provide an in-depth analysis of policy implications. These are both limitations, and potential follow-up activities. However, the report is complemented by 17 country-level snapshots, which describe in detail country specific trends.